A comparative study of student academic performance in on-campus teaching and distance learning in a Computer Engineering Programme (Journal of Science and Technology, 2016)
The purpose of this study was to examine the differences in academic performance of students in distance learning and on-campus programmes in a Computer Engineering programme at the Kwame Nkrumah University of Science and Technology, Ghana. The study employed descriptiveand inferential statistics for analysing the data from 76 students, drawn from the Computer Engineering Programme. The findings of the study suggested no significant differences of academic performance (Cumulative Weighted Average Scores) between distance and on-campus students. However there were statistically significant differences between the two groups in 20 of the 43 courses with the on-campus students scoring higher marks than the distance students. We found weak correlation between age, admission aggregates and CWA scores of on-campus and distance learning students in the two separate learning environments. The lack of a statistically significant correlation between the variables suggests that age and admission aggregates are not strong predictors of CWA scores in the two learning modes. It can be concluded that distance learning could be used as a viable alternative educational methodology for the delivery of computer engineering courses.